1997
DOI: 10.1093/qjmed/90.7.477
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxaemia in patients with hyperventilation syndrome

Abstract: We assessed 12 patients with hyperventilation syndrome (HVS) who had experienced hypoxaemia (PaO2 < 60 Torr or SaO2 < 90%) despite the lack of any other organic disease and variability in their blood gas data. Hypoxic and hypercapnic ventilatory responses were measured in nine. Eight of the 12 patients had been referred from other hospitals to our institution for hypoxaemia of unknown origin. Mean PaO2 (n = 12) at rest (non-attack stage) was 87.3 +/- 7.5 Torr (mean +/- SD). Their (n = 9) hypoxic (-0.53 +/- 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Given the absence of evidence for organic disease, the disorder seen in this patient was thought to involve a functional abnormality of the breathing pattern under cortical, or perhaps voluntary control. However, such abnormalities in breathing pattern attributed to cortical or psychological causes are typically seen in patients with hyperventilation syndrome [8,9]. This patient, however, showed hypercapnia with apnoea while awake.…”
Section: Discussionmentioning
confidence: 73%
“…Given the absence of evidence for organic disease, the disorder seen in this patient was thought to involve a functional abnormality of the breathing pattern under cortical, or perhaps voluntary control. However, such abnormalities in breathing pattern attributed to cortical or psychological causes are typically seen in patients with hyperventilation syndrome [8,9]. This patient, however, showed hypercapnia with apnoea while awake.…”
Section: Discussionmentioning
confidence: 73%
“…MacDonald’s case was reported as an example of a near-fatal instance of PHA. Chin reported hypoxemia and PHA in patients with HVS [13]. Three patients presented PHA, and their SaO 2 levels were 48%, 63%, and 68%.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was successfully treated with intubation and ventilation. Chin et al reported cases with HVS that presented long PHA and severe hypoxemia [13]. The treatments administered to the patients were not mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports that hypoxemia and hypercapnemia may occur in patients with apnea or hypopnea that is consistent with the apnea and hypopnea criteria established by the American Academy of Sleep Medicine (AASM), 16 and that in such cases the patient may hyperventilate to remedy the situation. 17 Based on these reports, we judged apnea and hypopnea to occur when there was a clear decrease in respiratory amplitude for more than 10 s, or when there was a decrease in amplitude of more than 30% compared with the normal respiratory waveform for more than 10 s and a forced respiratory waveform with an acute rhombus (or triangle) shape accompanying hyperventilation. There is a possibility of mistakes due to body movement if there is not a forced respiratory waveform when apnea and hypopnea are analyzed in the SD-101.…”
Section: Sd-101mentioning
confidence: 99%